Business Process Reengineering Pada Pengukuran Sistem Pemesanan Tiket Pesawat Maskapai Lion Air - Romadhana, Muhammad Restu Adjie; Nuryasin, Ilyas; Suharso, Wildan (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Air transportation is a very important sector in the context of economic and regional development. Aviation has a crucial role in supporting economic growth, global connectivity, and the advancement of other sectors. This research aims to understand and improve the efficiency of Lion Air Balikpapan airline ticket booking process through the application of Business Process Reengineering (BPR) method. This research method involves a series of steps in order to conduct BPR. Testing of throughput efficiency is done based on the calculation of business process performance time using ASME standard. The result of the initial analysis shows that the ticket booking process at Lion Air Balikpapan has a throughput efficiency of 38.42%. However, after making changes and mapping the ASME standard as well as eliminating processes that do not provide added value, the throughput efficiency increased to 90.99%. This shows a significant improvement in efficiency and speed in the ticket booking process. The conclusion shows that the application of BPR method in the ticket booking process of Lion Air Balikpapan airline successfully improves the efficiency and speed of service to customers.